The dark side of Section 63(3b) of the Labour Act (Chapter 28:01): The perspective of the stakeholders - Pilot Ndhlovu; Provilence Ndhlovu (Wiley, 2023)
This article sought to investigate the untold story of section 63(3b) of the Labour Act, Chapter 28:01 of Zimbabwe. A qualitative approach was used in this study. The purposive sampling method was used to select 30 participants. Semi-structured interviews were utilized to collect primary data from Zvishavane – Mberengwa area in the Midlands Province. The study established that employers have become knowledgeable of the Labour Act and are thus sidelining the Labour Officer for Designated Agents at the employees' expense. The research established that employees who are less favored by the set-up feel like Labour Officers are letting them down. The study revealed that section 63(3b) of the Labour Act was defeating the whole purpose of the act as it was only benefiting employers. Section 63(3b) of the Labour Act does not promote social justice and democracy as provided for in section 2A of the Labour Act. However, it was recommended that National Employment Councils should not deploy a Designated Agent in the first place if they are not able to deploy them in every district like what the government does on its Labour Officers. It was also recommended that the government and policymakers should consider amending the Labour Act, especially on the issue of jurisdiction; otherwise, the system will continue to suffocate one side.